Bilateral Stent Migration: A Rare Case Report - Dr. Sanjay P. Dhangar (SP’z Series New Insights on Urology and Urological Research Part I, 2022)
Double pigtail (DJ) ureteral stents are used to prevent ureteral obstruction and allow easy passage of urine. Stent migration is a well-recognized complication of stents, but migration into the renal pelvis is rarely documented. We present a case of simultaneous proximal and distal migration of a stent and discuss briefly, the etiological factors for the phenomenon and associated problems in management. Keywords: Stent Migration; Percutaneous Nephrostomy; Stent Complication.